The architecture of Perak Traditional Malay Roof Houses (PTMRH) in the year of 1820-1940 : a chronological analysis of the arabesque types on wall of rumah ibu / Norhasandi Mat ... [et al.] - Mat, Norhasandi; Monir, Ahmad Marzukhi; Abdul Rashid, Mohd Sabrizaa; Hanafi, Zulkifli (2012)
This paper qualitatively discussed about the decorative woodcarving on Perak Traditional Malay Roof Houses built between the years 1800-1940 looking from the perspective of the Malay belief in Islam. Perak wood carving on houses is considered decorative art of Islam which is known as arabesque. Arabesque may represent a thought process, an idea as well as an abstract representation of line and pattern on any material surface. It is a decorative element results from Islamic reaction against anything iconic or representational arts. Perak wood carving seems to carry both elements of flora and fauna limits itself to the framework of Islamic arts owes motif to predominantly Malay primordial belief. The „arabesque forces‟ vis-à-vis Islam that later took over the previous art of earlier belief, adopt and actualize the art of the earlier belief of the Perak Malay while, the Chinese migrant carpenter or tukang Cina (Chinese carpenter) carved motif in accordance to this belief system. Initially the Chinese tukang abide to rule and being accommodative for the sake of the survival of the carpentry enterprises. Prior to analysis, identification of carving types has been made through recognizing houses built by Malay and Chinese tukang or by both parties through interviewing process on the living tukang and elders in the villages. Three categories of PTMRH are identified in the discussion, the first was the earliest Malay houses which is the traditional version built solely by Malay tukang, the second version is the orang kebanyakan (ordinary Malay) and orang berada (Malay novelty) version built by the Malay tukang and the third was the innovative version built either by the Malay or by the Chinese alone or by joint effort of the two tukang. However, houses built by Malay and Chinese seem to have slight differences in construction as well as decorative aspects. Through visual observation, carving done by Malay is fluid or fine refers its motif to the surrounding environment while the Chinese carving is abstract, modular, to be as close as to the Malay counterpart reminiscent of Malay flora and fauna essence while carrying and applying (some Chinese abstract formal tendency) Chinese hidden geometrical structure to the carving that need further research.